Pregnancy outcomes and risk of endometrial cancer: A pooled analysis of individual participant data in the Epidemiology of Endometrial Cancer Consortium. Issue 9 (17th November 2020) - Jordan, Susan J.; Na, Renhua; Weiderpass, Elisabete; Adami, Hans‐Olov; Anderson, Kristin E.; van den Brandt, Piet A.; Brinton, Louise A.; Chen, Chu; Cook, Linda S.; Doherty, Jennifer A.; Du, Mengmeng; Friedenreich, Christine M.; et al.
Abstract: A full‐term pregnancy is associated with reduced endometrial cancer risk; however, whether the effect of additional pregnancies is independent of age at last pregnancy is unknown. The associations between other pregnancy‐related factors and endometrial cancer risk are less clear. We pooled individual participant data from 11 cohort and 19 case‐control studies participating in the Epidemiology of Endometrial Cancer Consortium (E2C2) including 16 986 women with endometrial cancer and 39 538 control women. We used one‐ and two‐stage meta‐analytic approaches to estimate pooled odds ratios (ORs) for the association between exposures and endometrial cancer risk. Ever having a full‐term pregnancy was associated with a 41% reduction in risk of endometrial cancer compared to never having a full‐term pregnancy (OR = 0.59, 95% confidence interval [CI] 0.56‐0.63). The risk reduction appeared the greatest for the first full‐term pregnancy (OR = 0.78, 95% CI 0.72‐0.84), with a further ~15% reduction per pregnancy up to eight pregnancies (OR = 0.20, 95% CI 0.14‐0.28) that was independent of age at last full‐term pregnancy. Incomplete pregnancy was also associated with decreased endometrial cancer risk (7%‐9% reduction per pregnancy). Twin births appeared to have the same effect as singleton pregnancies. Our pooled analysis shows that, while the magnitude of the risk reduction is greater for a full‐term pregnancy than an incomplete pregnancy, each additional pregnancy is associated with further reduction in endometrial cancer risk, independent of age at last full‐term pregnancy. These results suggest that the very high progesterone level in the last trimester of pregnancy is not the sole explanation for the protective effect of pregnancy. Abstract : What's new? Having a full‐term pregnancy reduces a woman's risk of endometrial cancer, perhaps due to a protective effect from high levels of progesterone in the third trimester. Here, the authors conducted a pooled analysis of 11 cohort studies and 19 case‐control studies to learn more about the effect of multiple pregnancies on endometrial cancer risk. They found that up to eight full‐term pregnancies each reduced endometrial cancer risk, independent of maternal age and oral contraceptive use. Interestingly, incomplete pregnancies were associated with a smaller reduction in risk, suggesting that high third trimester progesterone levels are not the only contributing factor.